Rapid response to a conjunctivitis outbreak: the use of technology to leverage information. - Pryor JH; Martin MT; Whitney CG; Turco JH; Baumgartner YY; Zegans ME (Journal of American College Health, 2002)
When an outbreak of conjunctivitis was identified at a rural New England college early in 2002, the college health center medical staff used various information management and communication systems to alert the community to the situation. They called upon the state Department of Human Services and the Centers for Disease Control and Prevention to help them understand and manage the outbreak. Technological systems already in place at the college allowed for rapid collection of data by means of a survey delivered over the Internet and a carriage study facilitated by a Web-based appointment and communication system. Within days, the data were collected and analyzed and an immediate response to contain the outbreak was launched.